Sistem Informasi Arsip Data Pengelolaan Sampah Berbasis Website Dengan Meggunakan Metode Prototipe - Rahayu, Maelani Dwi; Purwanto, Purwanto; Yuniar Laeli N.F (CV. ITTC INDONESIA, 2025)
Waste management is one of the crucial issues in maintaining cleanliness and environmental sustainability. In Banjarnegara Regency, the process of recording and archiving waste data is still carried out manually, which hinders data storage, reporting, and retrieval. This condition poses a risk of data loss and delays in information management processes. The DPKPLH (Department of Housing, Settlement Areas, and Environment) of Banjarnegara requires a system that can support a more structured and easily accessible waste data archiving process. This research aims to design and implement a web-based information system for waste data archiving at the DPKPLH Banjarnegara using the prototype development method. Data collection methods included interviews, observations, questionnaires, and literature studies, while the sampling technique used was purposive sampling, involving two respondents directly related to the system. The results of the questionnaire-based testing showed a user satisfaction level of 97.78%, categorized as “strongly agree.” The developed system is capable of improving the efficiency of recording, storing, and retrieving waste archive data, providing an easy-to-use interface, and ensuring that data can only be accessed by authorized personnel. Therefore, this information system has proven to enhance the effectiveness and efficiency of waste data archiving management at DPKPLH Banjarnegara.